Chapter Per la ritrattistica di Antonio Montauti. Tre busti inediti di eruditi fiorentini - Arba, Eleonora (Studi e saggi, 2020)
This paper presents for the first time three plaster sculptures made by the Florentine artist Antonio Montauti (1683-1746) and currently preserved at the Biblioteca Roncioniana in Prato. The subjects of these portraits are Tuscan literates and academics Anton Maria Salvini, Francesco Baldovini and Giovanni Battista Casotti. The three busts were most likely made around 1713: this date is indicated on Salvini's portrait, allowing us to speculate on the existence of a series of portraits of Florentine literates, much like Montauti's famous series dedicated to Tuscan illustrious men (Ficino and Machiavelli amongst others). These busts also give us the chance to take a further look at Montauti's style, unveiling his interest towards antique sculpture at such an early stage of his activity.